2022
DOI: 10.3390/cancers14041075
|View full text |Cite
|
Sign up to set email alerts
|

Test/Retest Reliability and Validity of Remote vs. In-Person Anthropometric and Physical Performance Assessments in Cancer Survivors and Supportive Partners

Abstract: (1) Background: Anthropometric and physical performance testing is commonly done in lifestyle research and is traditionally performed in-person. To expand the scalability of lifestyle interventions among cancer survivors, in-person assessments were adapted to remote means and evaluated for feasibility, safety, validity, and reliability. (2) Methods: Cancer survivors and supportive partners were approached to participate in three anthropometric and physical performance testing sessions (two remote/one in-person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 42 publications
2
19
1
Order By: Relevance
“…The greatest differences in validity were observed in the 8-foot up-and-go test with an ICC = 0.64 compared to an ICC = 0.80 observed in a previous study [26]. This could be due to the difference in the test performance, being higher in the present study than in the study focused on cancer survivors [26].…”
Section: Discussioncontrasting
confidence: 76%
“…The greatest differences in validity were observed in the 8-foot up-and-go test with an ICC = 0.64 compared to an ICC = 0.80 observed in a previous study [26]. This could be due to the difference in the test performance, being higher in the present study than in the study focused on cancer survivors [26].…”
Section: Discussioncontrasting
confidence: 76%
“…Handouts providing detailed set-up instructions were provided to the participants ahead of time. The selected objective physical function measures have been previously administered remotely in published studies by Blair et al, Guidarelli et al, and Hoenemeyer et al [ 30 , 31 , 60 ]. Blair et al have been using the 30 s chair stand test, which is similar to the five times sit-to-stand test in SPPB and the TUG test via videoconferencing in older survivors of cancer [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…They found good agreement with in-person tests (ICC = 0.88) for TUG and substantial agreement between repeat assessments for total SPPB score (Cohen’s kappa of 0.78) [ 30 ]. Hoenemeyer et al also found strong agreement (ICC = 0.74) for TUG and very strong agreement (ICC = 0.87) for the 2-min step test among cancer survivors and their partners [ 60 ]. Detailed descriptions of how the assessor set up the assessments are included in the Supplemental Material (Table S1) .…”
Section: Methodsmentioning
confidence: 99%
“…Virtual protocols were assessed for reliability and validity, and assessors were trained and evaluated for accuracy prior to initiation [53]. Zoom ® sessions are recorded to permit accuracy for timed performance testing, reduce the discrepancy introduced by differential transmission of sight and sound and inform periodic quality assurance evaluations among assessors.…”
Section: Recruitment Eligibility and Consentmentioning
confidence: 99%
“…The Senior Fitness Battery objectively assesses physical performance in several domains, is sensitive to change, devoid of ceiling effects, and has normative scores [52]. Typically done in-person, tests were adapted to virtual use, refined, and then evaluated for validity and reliability [53]; arm curls and grip strength, were not included given requirements for costly equipment and/or excessive postage.…”
Section: Physical Performance Testingmentioning
confidence: 99%